Systemic usury and the European Consumer Credit Directive - Doris Neuberger; Udo Reifner (Universität Rostock, Institut für Volkswirtschaftslehre, 2019)
Usury is a frequent occurrence in consumer credit markets and particularly affects low-income households. Systemic usury exploits poverty by shifting usury into additional products and leveraging usury gains by stringing together individual loan agreements. This paper reviews the economic rationale for usury legislation and on this basis evaluates the European Consumer Credit Directive 2008/48/EC. Systemic usury is a market failure. The most powerful explanations for such failure in consumer credit markets are monopoly power, where the consumer is locked in a bilateral credit relationship, discrimination through risk-based pricing, and negative externalities, where the least solvent borrowers are cross-subsidized by the more solvent ones. Incomplete information of consumers cannot explain systemic usury in credit markets, because even fully informed consumers would be discriminated and trapped into a situation of bilateral monopoly. However, the European Consumer Credit Directive is primarily based on the model of incomplete information, which it seeks to correct by informational duties. As a consequence, usurious practices and products are implicitly acknowledged as legal, which has eroded the national combat against usury. Therefore, this Directive is not effective and must be reformed.
Keywords: D14; D18; D42; D62; D63; G21; G28; K15; K22; K33; L12; L14; 330; discrimination; Consumer Credit Directive; incomplete information; payment protection insurance; overindebtedness; monopoly power; responsible lending; risk-based pricing; usury